Les retombées sociales du jardinage communautaire et collectif dans la conurbation de Québec - Manon Boulianne; Geneviève Olivier-d’Avignon; Vincent Galarneau (VertigO)
Based on an empirical study carried out in Quebec City and the vicinity, this article offers a comparative look at social impacts of community and collectives gardens for their local communities. Based on a review of pertinent research, four dimensions (socio-economic, socio-environmental, socio-spatial and socio-political) of the potential impacts of urban gardening were identified and put to test. Quantitative and qualitative data obtained through visits to garden sites, group interview and a questionnaire survey show that, contrary to the general belief, beyond specificities related to their respective mission, social impacts of community and collective gardens present more similarities than differences. According to the authors, this conclusion should be taken into account by the movement for the development of urban agriculture.